Development Program for assertive behavior in low socioeconomic stratum children in Metropolitan Lima - Lizano Espinoza, Carolina (2005)
The authors propose a program to develop and establish an assertive behavior in children at basis, regular primary school. This will be done through strength of values and moral judgment. The content of the program is explained, its methodology and its instruments.